A review of China’s compensation program for adverse reactions following immunization - Yingxiong, Wu (Frontiers in Public Health, 2023)
Vaccination is a compelling measure to battle infectious diseases and protect public health. However, because of the constraints on human cognition, it is difficult to ensure that vaccines are safe. Adverse reactions to immunization can cause individual injury. In numerous countries, no-fault programs have been established to compensate individuals for vaccine-related injuries. China also established a vaccine injury compensation system with its own unique characteristics. The Vaccine Administration Law was promulgated in 2019 to establish a compensation system for those who experience adverse reactions following immunization; nevertheless, the compensation system is imperfect. Even when the applicable terms are applied to deal with vaccine-related injuries, some issues remain, such as unreasonable diagnosis and evaluation procedures for adverse reactions, excessively strict standards regarding proof and inconsistent compensation standards across the country. Therefore, to provide effective compensation for vaccine recipients, it is important to clarify the standards of proof and establish a sensible vaccine injury compensation system that includes Corona Virus Disease 2019 vaccine-injury compensation.